The place of hormonal therapy in breast cancer treatment with taking into consideration the role of letrozole (Femara®) - Rolski, Janusz; Pawlicki, Marek (Contemporary Oncology/Współczesna Onkologia, 2002)
Hormonal therapy is appropriate treatment for allstages of estrogen - or progesterone-receptor-containing breast cancer for which systemic therapy is indicated. Against metastatic disease, initial endocrine treatments induce survival prolongation and objective tumor shrinkage in 20-40% of all patients (40-80% of estrogen receptor - positive patients). Another 10-20% of patients will have clinically significant periods of tumor stability. No single class of hormonal agents has been shown to be consistently superior as treatment of metastatic disease, so the choice of treatment is dictated by toxicity and effects on quality of life. As adjuvant therapy of early disease, tamoxifen and oophorectomy are the only hormonal treatments prospectively shown to decrease recurrence and mortality. Future prospects for hormonal treatment include development of additional predictors of response, new classes of drugs and more selective drugs to prevent as well as to treat the disease. New clinical trial data have strengthend support for the aromatase inhibitor letrozole as an new standard for hormone therapy in breast cancer. Letrozole (Femara®) is third generation aromataze inhibitor for use in postmenopausal women with hormonal-sensitive breast cancer. Letrozole was found to be at last as effective as megestrol acetate in the second-line treatment of postmenopausal women with advanced breast cancer who had failed tamoxifen therapy, according to the results of three large multicenter, randomized trials. Letrozole was also superior to tamoxifen in the first-line treatment of postmenopausal women with advanced breast cancer, according to the results of a multicenter, double-blind, randomized study. Letrozol was superior to tamoxifen in time to progression, reducing risk of progression by 30%. Moreover, letrozole was superior to tamoxifen in time to treatment failure. Overall response rate was higher for the aromatase inhibitor. A double-blind, randomized trial was recently conducted, to evaluate the activity of letrozole versus tamoxifen as preoperative endocrine therapy for postmenopausal women with estrogen-positive primary invasive breast cancer. Overall objective response rate was statistically significantly superior in the letrozole group. Breast conservation was possible in 48% of patient treated with letrozole compared to 36% of those treated with tamoxifen. Differences in response rates between the aromatase inhibitor and tamoxifen were more marked for tumors that were positive for erbB-1 and/or erbB-2. These data confirmed the high activity of letrozole in hormonal therapy of breast cancer.